2010
DOI: 10.1016/j.neubiorev.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species assessments of motor and exploratory behavior related to bipolar disorder

Abstract: Alterations in exploratory behavior are a fundamental feature of bipolar mania, typically characterized as motor hyperactivity and increased goal-directed behavior in response to environmental cues. In contrast, abnormal exploration associated with schizophrenia and depression can manifest as prominent withdrawal, limited motor activity, and inattention to the environment. While motor abnormalities are cited frequently as clinical manifestations of these disorders, relatively few empirical studies have quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 148 publications
1
44
0
2
Order By: Relevance
“…Moreover, both the behavioral and RT-PCR analysis data showed that drugs were absorbed well by zebra-fish larvae within a defined time period (1 hr pre-treated and 1 hr co-treated with PTZ, 2 hrs totally), and most false negative results could be avoided if maximum tolerant concentration was used. These results were consistent with Orellana-Paucar et al [17] and Baxendale et al [25] data. Therefore, for anticonvulsant drug screening, it does not need to treat zebra-fish larvae more than 2 hrs, especially in highthroughput screening.…”
Section: Page 6 Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, both the behavioral and RT-PCR analysis data showed that drugs were absorbed well by zebra-fish larvae within a defined time period (1 hr pre-treated and 1 hr co-treated with PTZ, 2 hrs totally), and most false negative results could be avoided if maximum tolerant concentration was used. These results were consistent with Orellana-Paucar et al [17] and Baxendale et al [25] data. Therefore, for anticonvulsant drug screening, it does not need to treat zebra-fish larvae more than 2 hrs, especially in highthroughput screening.…”
Section: Page 6 Ofsupporting
confidence: 92%
“…Numerous studies have showed that adult or zebra-fish larvae exposed to PTZ exhibit increased locomotor activity, seizure-like behavior, and epileptiform electrographic activity [15,19] [ [22][23][24], which have a good correlation between zebra-fish and rodent data [15,17,21,25]. Also, many researchers have used zebra-fish seizure model for anti- convulsions in zebra-fish larvae was assessed through quantification of the high-speed moved distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, the Ank-G cKO mice exhibit striking hyperactivity, one of the core features of human mania, and a translatable phenotype which can be assessed in comparable ways in human patients and in mouse models (43)(44)(45)(46). There was also increased exploratory behavior, decreased anxiety-like behavior, and decreased depression-like behavior, all comparable to behaviors characteristic of human mania.…”
Section: Discussionmentioning
confidence: 91%
“…NOTE: Some behavioral parameters (e.g., motor-and exploratory behavior) might be scored automatically as e.g., discussed by Henry et al 19 after necessary adjustment of the mHB.…”
Section: Behavioral Testing -Without the Presence Of Group Matesmentioning
confidence: 99%